A survey of nurses' awareness of infection control measures in Baranya County, Hungary - Sahar Hammoud; Haitham Khatatbeh; Afshin Zand; Béla Kocsis (Wiley, 2021)
Abstract Aim This study aimed to assess nurses' awareness of infection control (IC) measures in Baranya County, Hungary. Design A cross‐sectional survey. Methods The study used the infection control standardized questionnaire to assess nurses' awareness in standard precautions (SP), healthcare‐associated infections (HAIs) and hand hygiene (HH). Data collection was done from two hospitals in February and March 2020. SPSS was used for statistical analysis. Results The study included 121 nurses. The mean scores were 16.55 ± 2.69 for IC overall awareness, 10.10 ± 1.58 for SP, 2.07 ± 0.71 for HAIs and 4.38 ± 1.47 for HH. Acceptable scores were reached in overall awareness and SP. The overall and HAIs' scores significantly differed across educational degrees. The difference in SP mean ranks was statistically significant across hospital types. The low HAIs and HH scores highlight the need to enhance IC trainings in Hungarian hospitals and improve nurses' knowledge on IC.